2015
DOI: 10.3390/rs70202208
|View full text |Cite
|
Sign up to set email alerts
|

Landsat-8 Operational Land Imager (OLI) Radiometric Performance On-Orbit

Abstract: Expectations of the Operational Land Imager (OLI) radiometric performance onboard Landsat-8 have been met or exceeded. The calibration activities that occurred prior to launch provided calibration parameters that enabled ground processing to produce imagery that met most requirements when data were transmitted to the ground. Since launch, calibration updates have improved the image quality even more, so that all requirements are met. These updates range from detector gain coefficients to reduce striping and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 14 publications
2
99
0
Order By: Relevance
“…The OLI imagery has seven multi-spectral bands in VIS-SWIR region at 30-m spatial resolution [40]. In comparison with other Landsat systems (TM and ETM+), the OLI has a new "deep blue" band, which may provide additional information about soil properties in this study.…”
Section: Satellite Imagery and Preprocessingmentioning
confidence: 99%
“…The OLI imagery has seven multi-spectral bands in VIS-SWIR region at 30-m spatial resolution [40]. In comparison with other Landsat systems (TM and ETM+), the OLI has a new "deep blue" band, which may provide additional information about soil properties in this study.…”
Section: Satellite Imagery and Preprocessingmentioning
confidence: 99%
“…It is important to study continuity among sensors from the same series of satellites by considering of the important parameters including sensor characteristics, over-pass time, scanning system, angular affect and etc. A few studies related to the continuity of Landsat 8 have been conducted, including preflight and post-launch calibrations [28][29][30][31][32][33]. Most of these studies have shown that the continuity between the Landsat-8 OLI and Landsat-7 ETM+ is good.…”
Section: Introductionmentioning
confidence: 99%
“…10 OLI is the most advanced radiometer ever flown on a Landsat platform, with SNRs roughly an order of magnitude higher than the predecessor Enhanced Thematic Mapper Plus (ETMþ) instrument of Landsat-7 and 12-bit rather than 8-bit digital resolution. 11 The SNRs reported for OLI or ETMþ, however, are based on radiances typical of land observations. To assess potential OLI performance over oceans, the sensor noise model 11 was applied to typical radiances (Ltyp) interpolated from values reported in Ref.…”
Section: Data and Sensor Characteristicsmentioning
confidence: 99%